2018
DOI: 10.1002/jcb.26894
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: LncRNA ATB promotes proliferation and metastasis in A549 cells by down‐regulation of microRNA‐494

Abstract: Lung cancer is a commonly diagnosed disease with poor prognosis. Novel therapeutic targets and deep understanding of the regulatory mechanisms in lung cancer are of great importance. We aimed to figure out the functional roles of lncRNA-activated by transforming growth factor-β (ATB) in A549 cells as well as the underlying molecular mechanisms. ATB was non-physiologically expressed in A549 cells after cell transfection. Then, cell proliferation, expressions of proteins related to proliferation and epithelial-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
1
28
2
Order By: Relevance
“…The effects of lncRNA‐ATB on viability and migration of HMEC‐1 cells were consistent with that on other cell lines reported previously. For examples, A549 cell proliferation and metastasis are promoted by lncRNA‐ATB . Likewise, there is a close correlation between high expression of lncRNA‐ATB and elevated migration and invasion in renal cell carcinoma cells …”
Section: Discussionmentioning
confidence: 99%
“…The effects of lncRNA‐ATB on viability and migration of HMEC‐1 cells were consistent with that on other cell lines reported previously. For examples, A549 cell proliferation and metastasis are promoted by lncRNA‐ATB . Likewise, there is a close correlation between high expression of lncRNA‐ATB and elevated migration and invasion in renal cell carcinoma cells …”
Section: Discussionmentioning
confidence: 99%
“…It is possible that lncRNA-ATB is an example of this type of non-coding RNA. However, according to previous studies ( 25 , 31 ), it was noted that lncRNA-ATB serves an oncogenic role in the majority of types of cancers. In line with these previous studies, the present study identified that lncRNA-ATB was significantly upregulated in MM cell lines compared with normal human epidermal melanocyte cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…In line with these previous studies, the present study identified that lncRNA-ATB was significantly upregulated in MM cell lines compared with normal human epidermal melanocyte cell lines. In non-small cell lung cancer, lncRNA-ATB promotes cellular apoptosis, and inhibits cell viability, cell migration and invasion ( 31 ). Furthermore, lncRNA-ATB was identified as a potential oncogene in osteosarcoma ( 32 ), glioma ( 33 ), prostate cancer ( 34 ) and colon cancer ( 35 ); the upregulation of lncRNA-ATB was able to promote carcinogenesis and progression in these cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that ATB acts as a competing RNA by binding with microRNA (miR)-494 in lung cancer cells (28), miR-141-3p in gastric cancer cells (29), miR-590-5p in melanoma (30), and miR-200 family members in diverse types of cancer (18,26,31,32). ATB regulates transcriptional coactivator YAP1 (YAP1), NF-κB, p38 mitogen-activated protein kinase (MAPK), Twist, and TGF-β in lung cancer, glioma, breast cancer and malignant melanoma (23,30,33,34).…”
Section: Discussionmentioning
confidence: 99%